Struktur Kurikulum Akidah Akhlak MTs: Analisis Holistik Prinsip Kurikulum Spiral Dalam Pembentukan Karakter Siswa - Nasrul HS; Fitriyani; Ainul Zaskia; Aisyah Nurhikmah (Atha Publishing Globalindo, 2025)
Aqidah Akhlak education in Islamic Junior High Schools (MTs) plays a strategic role in shaping students' character amidst the challenges of moral degradation and the complexity of adolescent life in the digital era. However, the implementation of the Aqidah Akhlak curriculum still faces a gap between the ideal design and learning practices, particularly in the application of the spiral curriculum principle that emphasizes meaningful repetition and continuous deepening of values. This study aims to holistically analyze the structure of the Aqidah Akhlak curriculum in MTs and its level of conformity with the principles of the spiral curriculum in shaping students' character. The study used a qualitative approach with a descriptive-holistic analysis design implemented in several MTs in Pekanbaru City. Data were collected through in-depth interviews, classroom observations, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the structure of the Aqidah Akhlak curriculum has been arranged in stages from grades VII to IX and reflects the spiral principle through the introduction, deepening, and internalization of aqidah and moral values. Learning is supported by meaningful repetition, the integration of faith and moral values, madrasah culture, and the role of teachers as murobbi. However, the implementation of the spiral curriculum has not been fully systematic due to limited operational guidelines, teacher administrative burdens, and synchronization between levels. This study concludes that the spiral-based Akidah Akhlak curriculum has strong potential to strengthen Islamic character education, but requires strengthened curriculum planning, teacher pedagogical training, and institutional support for more consistent and effective implementation.